2017
DOI: 10.1002/term.2310
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printed polycaprolactone-based scaffolds provide an advantageous environment for osteogenic differentiation of human adipose-derived stem cells

Abstract: The capacity of bone grafts to repair critical size defects can be greatly enhanced by the delivery of mesenchymal stem cells (MSCs). Adipose tissue is considered the most effective source of MSCs (ADSCs); however, the efficiency of bone regeneration using undifferentiated ADSCs is low. Therefore, this study proposes scaffolds based on polycaprolactone (PCL), which is widely considered a suitable MSC delivery system, were used as a three-dimensional (3D) culture environment promoting osteogenic differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…We observed that after 14 d of culturing ASCs on PCL þ 5%TCP, osteogenic differentiation increased compared to undifferentiated ASCs cultured in standard culture medium. The results thus obtained are consistent with those of previous studies reporting an increase in ALP activity after 14 d of ASC differentiation on scaffolds [37][38][39][40][50][51][52][53]. We also observed that modification of scaffolds can influence the degree of cell differentiation.…”
Section: Evaluation Of the Osteogenic Potential Of Cervical Fat From supporting
confidence: 92%
“…We observed that after 14 d of culturing ASCs on PCL þ 5%TCP, osteogenic differentiation increased compared to undifferentiated ASCs cultured in standard culture medium. The results thus obtained are consistent with those of previous studies reporting an increase in ALP activity after 14 d of ASC differentiation on scaffolds [37][38][39][40][50][51][52][53]. We also observed that modification of scaffolds can influence the degree of cell differentiation.…”
Section: Evaluation Of the Osteogenic Potential Of Cervical Fat From supporting
confidence: 92%
“…The supplementation of the culture medium with platelet lysate or platelet-rich plasma also improved the osteogenic differentiation of Ad-MSCs [ 14 , 22 , 23 ]. Also, the cultivation on three-dimensional scaffolds further improved the osteogenic properties of Ad-MSCs [ 24 , 25 ], amongst others, through the control of cell agglomeration [ 26 ]. Furthermore, co-cultivation with endothelial cells, vascular cells, or osteoblastic cells improved the osteogenic differentiation of Ad-MSCs [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matrices with strictly defined parameters can also be obtained using a variety of innovative 3D printing technologies [21][22][23]. One well-known method is the extrusion of polymers from melt.…”
Section: Introductionmentioning
confidence: 99%